Pengaruh Orientasi Pasar, Inovasi Dan Kreativitas Produk Terhadap Kinerja Industri Kreatif Untuk Mencapai Keunggulan Bersaing: (Studi pada Industri Kreatif yang Tergabung dalam Malang Creative Fusion) - Anjaningrum, Widiya Dewi; Sidi, Agus Purnomo (LP2M Institut Teknologi dan Bisnis Asia Malang, 2018)
This study aims to determine the effect of market orientation and product creativity on the product innovation, the effect of market orientation, innovation, and product creativity on competitive advantage, and the effect of competitive advantage on industrial performance. This research is a field research on creative-preneur in Malang town, especially those who are members of Malang Creative Fusion (MCF). The number of samples taken was 133 people that selected using an accidental purposive sampling technique. The results showed that market orientation and product creativity have a positive and significant effect on product innovation. On the other hand, market orientation, innovation and product creativity also have a positive and significant effect on competitive advantage. In addition, competitive advantage is also has a positive and significant effect on industrial performance. The implications of the research are to achieve high industrial performance, creative industry should improve the competitive advantage by improving the market orientation, innovation and product creativity. While to improve market orientation, innovation and product creativity, creative industries should know what the customers want, how the strategy of the competitor is and improve cross-functional functions. Besides it, creative industries should invent new products that are original, unique, and have a high attractiveness or at least develop existing products, make a differentiation of the products and sell them at competitive prices.